Drug eruptions at five institutes in Bangkok - Siripen Puavilai (2018)
The study was performed in five hospitals in Bangkok for a period of one year. All in- and outpatients who developed drug eruption from January to December 2001 were enrolled into the study. Physical examinations and complete history-taking were performed by one of the authors. A skin biopsy was done to confirm the diagnosis in every suspected case. Oral challenge test was performed to obtain a definite diagnosis only in some patients with informed consent. Among 212 patients, the most common causative drugs were antimicrobial agents with cephalosporin group in the highest rank. Maculopapular rash was the most common type of drug eruption followed by urticaria and photosensitivity reaction. It was concluded that antimicrobial agents were the predominant causative agents and maculopapular eruption was the most frequent clinical manifestation. New kinds of antimicrobial agents, anti-inflammatory drugs and lipid lowering agents could cause various patterns of drug eruption.